Interference With Redox Homeostasis Through a G6PD-Targeting Self-Assembled Hydrogel for the Enhancement of Sonodynamic Therapy in Breast Cancer - Huang, Cuiqing; Xu, Yuan; Wang, Duo; Chen, Zerong; Fang, Weimin; Shi, Changzheng; Xiao, Zeyu; Luo, Liangping (Frontiers in Chemistry, 2022)
Sonodynamics has emerged as a new potential therapy for breast cancer in recent years. However, GSH-mediated redox systems in cancer cells make them tolerable to oxidative stress-related therapy. Herein, in this study, with G6PD, the gatekeeper enzyme of the pentose phosphate pathway, as the regulative target, a self-assembled thermosensitive chitosan-pluronic hydrogel coloaded with ICG (sono-sensitive agent) and RRx-001 (IR@CPGel) was successfully prepared to enhance SDT through interference with redox homeostasis. Both in vitro and in vivo antitumor investigations verified that when integrated with sonodynamic therapy applied in breast cancer treatment, local administration of IR@CPgel could enhance ROS generation under LIFU irradiation and trigger the intrinsic apoptotic pathway of cancer cells, thus effectively inhibiting tumor growth in a safe manner. Moreover, RRx-001 may interfere with redox homeostasis in cancer cells by downregulating G6PD expression. Due to this redox imbalance, proapoptotic signals, such as P21 and p53, were enhanced, and metastasis-related signals, including MMP-2, ZEB1 and HIF-1α, were effectively reduced. Taken together, this work aimed to enhance the efficacy of sonodynamic therapy through local administration of self-assembled IR@CPGel to interfere with redox homeostasis and thus amplify the oxidative stress microenvironment in tumor tissues. In a word, this work provides a new strategy for the SDT enhancement in breast cancer therapy.